THE ACTUALISATION OF RĀMĀYAṆA'S ASTA BRATA LEADERSHIP TEACHINGS IN EDUCATION AND THE GLOBALIZATION ERA - Ni Ketut Srie Kusuma Wardhani; Gusti Ayu Agung Riesa Mahedradhani (UHN I Gusti Bagus Sugriwa Denpasar, 2025)
The Ramayana, a revered Hindu epic, offers profound insights into leadership through its Asta Brata principles. These principles, rooted in moral and spiritual values, outline essential qualities for effective leadership. Sri Rama, depicted as an avatar of Vishnu and an exemplary leader, embodies virtues such as truth, righteousness, humility, and courage. Asta Brata emphasizes key aspects of leadership. Economic empowerment ensures leaders promote the material well-being of their followers while maintaining fairness and justice. Empathetic leadership encourages seeing followers as cultured individuals deserving spiritual fulfillment, not just subordinates. Steadfastness (Bayu Brata) in principles and empathy towards followers' struggles are crucial. Knowledge excellence (Casi Brata) stresses leaders' need for superior understanding to guide communities effectively. Inspirational motivation (Agni Brata) ignites dedication among followers towards collective goals. In today's globalized world, these teachings remain relevant. They provide a timeless framework for ethical leadership in education and organizational management. Integrating Asta Brata principles enables leaders to foster societal progress while preserving moral and spiritual values amidst technological advancements. Overall, Asta Brata from the Ramayana guides leadership excellence with integrity and wisdom. It serves as a beacon for navigating contemporary challenges, contributing to holistic community and national development. Thus, embracing these principles ensures leaders not only lead effectively but also inspire and empower others towards collective prosperity and well-being.